Effects of Fixed and Removable Space Maintainers on Dental Plaque and DMFT/dft Values - Gurcan, Aliye Tugce; Koruyucu, Mine; Kuru, Sinem; Sepet, Elif; Seymen, Figen (Odovtos - International Journal of Dental Sciences, 2020)
Purpose: Space maintainers are important for the health and placement of children’s primary and permanent teeth. However, plaque and caries levels can be negatively affected when a dental appliance is in the mouth. This study aims to evaluate the oral health of pediatric patients that have space maintainers applied as a result of early tooth loss. Methods: This study included 100 systemically healthy patients between the ages of 4-15 years that were treated with space maintainers due to early loss of teeth. Decayed, missing, filled tooth index values and dental plaque status of the participants were recorded. Controls were performed in the 6th and 12th month. The index results were compared and evaluated statistically using ANOVA and paired-t-tests. Results: A total of 116 space maintainers, including 36 band and loops, 16 lingual arches, 21 palatal arches, 43 removable appliances, were evaluated in the study. Statistically significant differences were found between the pre-treatment and post-treatment index values (p<0.001). In the group of band and loops and removable space maintainers; the increases in DMFT/dft values of 6th month and 12th month according to initial DMFT/dft values were statistically significant (p<0.05). For plaque index, the increase in 12th month of all types of appliances were found statistically significant (p<0.001). The greatest increase in plaque index level was seen in the teeth of patients that had been treated with a lingual arch. Conclusions: Incompatible space maintainers can lead to caries, increased plaque accumulation, demineralized areas, and periodontal problems. The accumulation of plaque and difficulty of cleaning the teeth, especially in the fixed space maintainers, negatively affects the health of teeth. For this reason, good oral hygiene should be provided to patients and controls should be regularly performed.